Traditional Islamic Legal Epistemology in Pesantren’s Practice of Ḥisāb - Marwadi Marwadi; Eva Mir'atun Niswah; Muhammad Fuad Zain; Ahmad Rezy Meidina; Muhammad Akmal Kafi (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2025)
This study examines the epistemological basis behind the choice of four traditional Islamic boarding schools affiliated with Nahdlatul Ulama (NU) in East Java to prioritize ḥisāb (astronomical calculations) over ru'ya (crescent sighting) in determining the beginning of the Hijri month, even though NU institutionally prioritizes ru'ya. Through qualitative, empirical-legal research based on interviews, document analysis, and field observations, this study shows that the practice of ḥisāb is not merely a technical choice, but rather an expression of an epistemic orientation rooted in classical astronomical literature, the continuity of scientific chains of narration, and burhānī reasoning that emphasizes rational certainty. The use of ḥisāb is legitimized by classical al-Shāfi'iyya fiqh and the pesantren ethos, which emphasizes that knowledge must be put into practice (taṭbīq al-‘ilm). Thus, ḥisāb functions as a marker of scholarly authority, legal certainty, and the pesantren's institutional identity. Despite technical variations, all four pesantren demonstrate a common epistemological commitment: the integration of the bayānī textual approach with the burhānī scientific rationality. This study highlights how traditional institutions negotiate textual authority and scientific rationality in contemporary religious practice.